Transformation von Multiphysics-Modellen in einen FPGA-Entwurf für den echtzeitfähigen HiL-Test eingebetteter Systeme - Köllner, Christian (KIT Scientific Publishing, 2013)
This work establishes an integrated tool chain from modeling physical simulations to design automation for FPGA-based real-time simulations. Modelica was chosen as a versatile, intuitive and object-oriented modeling language. The implemented tool chain incorporates high-level synthesis methods to generate a VHDL design. Both floating-point and fixed-point arithmetic are supported.